Analisis Faktor yang Mempengaruhi Kepatuhan Wajib pajak Bumi Bangunan Terhadap Sanksi Pajak - riskiana, Nadia; Khoiri Furqon, Imahda (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2021)
This study aims to analyze the effect of taxpayer attitudes, taxpayer awareness, and sanctions against taxpayers, on taxpayer compliance in paying land and building taxes. The data obtained is in the form of data from the regional office of the tax directorate general. The analysis method used is descriptive quantitative r. The test results show that partially the attitude of taxpayers has no significant effect on taxpayer compliance, taxpayer awareness has a significant effect on taxpayer compliance, tax knowledge has a significant effect on taxpayer compliance, and simultaneously the attitude of taxpayers, taxpayer awareness, and tax sanctions have a significant effect on taxpayer compliance.